Aneuploidy induced in lymphocytes of parents of trisomic 21 children - Caria, H (2015)
A possible predisposition to aneuploidy in trisomic 21 individuals, their parents, and a control group was evaluated. Peripheral blood lymphocytes from those three groups were used to study the induction of micronuclei (MN) by mitomycin C, cyclophosphamide, and quercetin. Induced MN were further analysed by C-banding and CREST antibody. Trisomic 21 individuals have spontaneous frequencies of MN significantly higher than their parents and the control group. Quercetin without metabolic activation induces MN in trisomic 21 and their parents at a significantly higher level than in control group. The group of the parents of trisomic 21 individuals exhibits higher frequencies of induced MN by mitomycin C and cyclophosphamide than controls. Mitomycin C significantly induced CREST-positive-MN in ten of the sixteen parents evaluated. The results obtained seem to suggest a unique behaviour for the parents of trisomic 21 patients consisting in an increased susceptibility to chromosome loss in the presence of clastogenic genotoxicants, suggesting a higher predisposition to aneuploidy. Teratogenesis Carcinog. Mutagen. 21:369-382, 2001. (C) 2001 Wiley-Liss, Inc.